2014
DOI: 10.1111/jth.12573
|View full text |Cite
|
Sign up to set email alerts
|

High levels of procoagulant factors mediate the association between free thyroxine and the risk of venous thrombosis: the MEGA study

Abstract: To cite this article: Debeij J, van Zaane B, Dekkers OM, Doggen CJM, Smit JWA, van Zanten AP, Brandjes DPM, B€ uller HR, Gerdes VEA, Rosendaal FR, Cannegieter SC. High levels of procoagulant factors mediate the association between free thyroxine and the risk of venous thrombosis: the MEGA study. J Thromb Haemost 2014; 12: 839-46.Summary. Background: Thyroid hormone affects the coagulation system, but its effect on clinical disease is not clear. We determined the associations of levels of free thyroxine (FT4), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(49 citation statements)
references
References 35 publications
(48 reference statements)
3
44
0
Order By: Relevance
“…In line with the predominantly clinical studies published so far on this topic [8185], our proteome analysis demonstrated several proteins involved in the coagulation cascade to exhibit FT 4 -associated plasma levels (Fig. 4); these findings have been published separately [86].…”
Section: Resultssupporting
confidence: 86%
“…In line with the predominantly clinical studies published so far on this topic [8185], our proteome analysis demonstrated several proteins involved in the coagulation cascade to exhibit FT 4 -associated plasma levels (Fig. 4); these findings have been published separately [86].…”
Section: Resultssupporting
confidence: 86%
“…High levels of fT4 were also associated with the risk of VTE, up to an OR of 2.2 (95% CI 1.0-4.6) for levels above 24.4 pmol/L relative to fT4 levels between 15.5 and 18.9 pmol/L. Low TSH levels were also, but less evidently, associated with thrombosis, while there was no association with antiTPO and VTE risk [19].…”
Section: Rycina 3 Wartości Inr Dla Pacjentów Z Niskim Lub Prawidłowymentioning
confidence: 90%
“…The relatively low values of FT 4 in the population undergoing bariatric surgery are striking [median (IQR): 13 (12-14) pmol/l in both cases and controls]. The median FT 4 level in the study of Debeij et al [8] was 17.7 pmol/l, and in the MEGA Study [1], which was a large case-control study investigating risk factors for VTE, the median FT 4 level was 16.6 pmol/l in the controls. The literature about the association between (morbid) obesity and levels of FT 4 is limited, but it seems that lower levels of FT 4 are associated with higher BMI, suggesting that thyroid function (also within the normal range) could be one of several factors acting in concert to determine body weight in a population [13,14].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have indicated that thyroid hormone also influences the hemostatic balance and that these changes are associated with a risk of venous thromboembolism (VTE) or bleeding. Higher plasma levels of free thyroxine (FT 4 ) have been associated with an increased VTE risk [1,2,3]. Conversely, lower levels of FT 4 seem to be associated with a bleeding tendency [4,5].…”
Section: Introductionmentioning
confidence: 99%